QASHQADARYO VILOYATINING YIRIK SUV OMBORLARI VA ULARDA UCHRAYDIGAN BALIQLAR - Cho‘liev O.J., Cho‘liev O.J.; Ruziyev B.X. , Ruziyev B.X.; Mulkanov Y.M., Mulkanov Y.M. (Actual problems and prospects of the study of the fauna, 2024)
There are about 10 reservoirs in Kashkadarya region, the largest of which are Pachkamar, Chimkurgan, Qamashi, Hisorak and Talimarjon reservoirs. In this chapter of the work, we found it necessary to describe the large water reservoirs in our region. There are 11 species of fish in the reservoirs of Kashkadarya region, 6 of these species are acclimatized, and 5 are local species. 4 species of acclimatized fish (Carassius auratus gibelio, Ctenopharyngodon idella, Hypophthalmichthys molitrix, Stizostedion lucioperca) were introduced for specific purposes, while 2 species (Abramis brama, Channa argus) accidentally entered the water bodies of Uzbekistan.